Isolation and characterization of Borna disease agent cDNA clones. - Lipkin, W I (1990)
Borna disease (BD) is a neurologic syndrome characterized by behavioral disturbances and the accumulation of specific proteins in limbic system neurons. A viral etiology has been proposed because BD can be induced in birds, rodents, and primates by inoculation with filtered brain homogenates from animals with BD. We report here the isolation and preliminary characterization of cDNA clones from a rat with BD. These clones hybridized to specific transcripts in BD rat brain and arrested in vitro translation of BD proteins. In situ hybridization experiments using RNA probes prepared from these clones showed an abundance of these transcripts in limbic system neurons. Northern (RNA) hybridizations using these RNA probes indicated that the BD agent is probably a virus with major transcripts of 8.5, 2.1, and 0.8 kilobases.